1981
DOI: 10.1152/ajpgi.1981.241.5.g349
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes related to functional activity in gastric oxyntic cells

Abstract: When stimulated to secrete HCl the gastric oxyntic cell undergoes profound morphological change. The identifiable apical cell surface is greatly expanded in the stimulated oxyntic cell as compared with nonsecreting ones. To account for this change, one hypothesis proposes that the expanded surface is derived from the fusion of cytoplasmic tubulovesicular membranes with the existing limited apical membrane surface. An alternative hypothesis suggests that the tubulovesicular compartment is actually confluent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 0 publications
4
72
0
Order By: Relevance
“…37,41 Electron microscopy confirmed the activation-like pattern in the unstimulated Ae2 a,b Ϫ/Ϫ parietal cell, but with a well-developed tubulovesicular system and collapsed canaliculi ( Figure 8A) that resemble recycling early secretory elements. 39 These changes were accompanied by mitochondrial alterations with intramitochondrial holes and distorted cristae and increased numbers of lysosomes. Subcellular alterations in the Ae2 a,b Ϫ/Ϫ parietal cell worsened with secretory stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,41 Electron microscopy confirmed the activation-like pattern in the unstimulated Ae2 a,b Ϫ/Ϫ parietal cell, but with a well-developed tubulovesicular system and collapsed canaliculi ( Figure 8A) that resemble recycling early secretory elements. 39 These changes were accompanied by mitochondrial alterations with intramitochondrial holes and distorted cristae and increased numbers of lysosomes. Subcellular alterations in the Ae2 a,b Ϫ/Ϫ parietal cell worsened with secretory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, this was the case in our unstimulated wild-type parietal cells (Figure 7). However, unstimulated Ϫ/Ϫ parietal cells showed well-developed tubulovesicular system and collapsed canaliculi with no lumen (Figure 8A), that resemble recycling early secretory elements 39 ; moreover, mitochondria appeared concentrated at the cell periphery in these unstimulated Ae2 a,b Ϫ/Ϫ parietal cells ( Figure 8A). On stimulation, Ae2 a,b Ϫ/Ϫ parietal cells showed alterations of the tubulovesicular system, which varied in severity from collapsed canaliculi and decreased number of tubulovesicles ( Figure 8B) to highly distorted canaliculi ( Figure 8C).…”
Section: Morphological Alterations Of Parietal Cellsmentioning
confidence: 99%
“…Since our initial studies with monoclonal antibodies 3A6 and 4 F l l showed that antigenicity was not preserved after osmium tetroxide treatment, a conventional double-fixation procedure could not be used to determine the exact position of the gold particles on the section relative to the tubulovesicular membranes. To overcome this problem we employed a novel post-embedding approach of combining Thiery staining [33], to visualise the carbohydrate component of the luminal face of the membrane [41], with immunogold labelling to detect the antigenic sites. After combined immunolabelling/Thiery staining, the majority of the gold particles, representing the accessible 4F11 binding sites, were either superimposed upon (Fig.…”
Section: Production Of Monoclonal Antibodiesmentioning
confidence: 99%
“…In resting parietal cells, the H+ /K+-ATPase is predominantly retained within intracellular tubulovesicles where it is inactive due to the low K+ i 1997 by The American Society for Cell Biology permeability of the tubulovesicle membrane (Forte et al, 1981;Smolka et al, 1983). Upon stimulation, a 5-to 10-fold increase in the apical surface area and a corresponding decrease in the abundance of intracellular tubulovesicles is observed (Helander and Hirschowitz, 1972;Forte et al, 1981). As a result of this membrane reorganization, the intracellular H+ /K+-ATPase is translocated to the membranes of the secretory canaliculi.…”
Section: Introductionmentioning
confidence: 99%